Antibacterial (Staphylococcus aureus and Escherichia coli) and Antifungal (Saccharomyces cerevisiae) Activity Assay on Nanoemulsion Formulation of Ethanol Extract of Mangosteen Leaves (Garcinia mangostana L.) as Fruit Preservative - Diniatik Diniatik; Rosiana Sofia Anggraeni (Journal of Food and Pharmaceutical Sciences, 2021)
Fruits after harvesting will decay faster if not handled properly. Fruits can be demaged by bacterial and fungal. Mangosteen leaves contain xanthons which are antibacterial and antifungal. 50% ethanol extract of mangosteen leaves is formulated in Nanoemulsion preparations using the SNEDDS (Self-Nanoemulsifying Drug Delivery System) method. The mangosteen leaves 50% ethanol extract nanoemulsion formulation consisted of VCO (Virgin Coconut Oil) as oil, tween 80 as surfactant, and PEG 400 as cosurfactant. There are 3 formulations with variations in the concentration of mangosteen leaves ethanol extract, there are concentrations of 1%, 2%, and 3%. All formulations have a T% of more than 90%. The results of the particles measurement of nanoemulsion using PSA were in formulation 1 amounting to 16.1 nm; formula 2 is 16.7 nm; and formula 3 is 16.6 nm. The zeta potential characterization shows that formula 1 has a zeta value of -40.9 mV. The three formulations had a pH of 5. The largest inhibitory zone in the mangosteen leaf ethanol extract against S.aureus and E. coli bacteria were 11.08 mm and 5.87 mm respectively. Whereas in the S. cerevisiae antifungal test there was no inhibition zone at all concentrations. In the antibacterial and antifungal tests nanoemulsion preparations did not produce inhibitory zones in each concentration. Nanoemulsion preparations can retain the quality of strawberries when compared to the non-nanoemulsion preservative group, both in room storage and refrigerator temperature. The best preservative result is when the fruit is coated with nanoemulsion preservative and stored in refrigerator temperature.